Asymmetric access to the smallest enolate intermediate via organocatalytic activation of acetic ester - Chen, Shaojin (2014)
An NHC-catalyzed activation of acetic esters to afford enolate intermediates is disclosed. The catalytically generated triazolium enolate intermediates serve as two-carbon nucleophiles that undergo highly enantioselective reactions with enones and α,β-unsaturated imines to give α-unsubstituted δ-lactones and lactams, respectively.